CHARACTERISTICS AND STRATEGIES TO IMPROVE CHINESE OUTBOUND TOURIST TRAVEL TO INDONESIA - Hendriyani, I Gusti Ayu Dewi (Institut Pariwisata dan Bisnis Internasional, 2018)
The tourism sector in Indonesia has been established as the main sector in the future. Visits of Chinese tourists ranked highest in 2017 than any other country. The huge potential of China's market in the world demands that the government together with tourism stakeholders jointly increase the number of Chinese tourists visiting Indonesia. This research is a literature study on the characteristics of Chinese outbound tourists from various sources, as well as strategies to increase the visit of Chinese tourists to Indonesia. The results of this literature review are expected to be an input for the development of tourism sector in Indonesia in reaching outbound tourists from China, and can be an inspiration for a suitable research theme in the future.